PREVALENCE OF ANTIBODY TO HEPATITIS A IN ICELAND IN RELATION TO AGE, SEX, AND NUMBER OF NOTIFIED CASES OF HEPATITIS - BRIEM, HARALDUR; WEILAND, OLA; FRIDRKSSON, INGTHOR; BERG, REBEKKA (Oxford University Press, 1982)
The prevalence of antibody to hepatitis A virus (anti-HAV) was investigated in 623 outpatients in iceland. No difference in anti-HAV prevalence according to sex or rural vs. urban residence was found. The prevalence rates in different age groups were found to be comparable to those in the Scandinavian countries, increasing from 1.6% (1/63) in persons below 20 years of age to 66% (51/77) in persons above 60 years of age. The numbers of notified cases of hepatitis (epidemic jaundice) in iceland during the 20th century showed a pattern of repeated epidemics up to the early 1950s, after which low rates were noted. The incidence of hepatitis dropped 30-fold during the 20th century. Persons bom after the latest epidemic in 1952 were positive for anti-HAV in only 4.7% (7/150).